Othello - Shakespeare, William (New York : Bantam Classic, 2005)
Tells of the naive Moor who is successfully manipulated by the ambitious and deceitful Iago.
Keywords: Othello -- (Fictitious character from Shakespeare) -- Drama; Interracial marriage -- Drama